Placental site trophoblastic tumor – A rare gestational trophoblastic disease: A case report and review of literature - Prachi; Hema Malini Aiyer; Gaurav Sharma (Current Medical Issues, 2024)
Placental site trophoblastic tumor (PSTT) represents a rare form of gestational trophoblastic disease. It occurs commonly in females with a history of miscarriage, termination of pregnancy, or any other ongoing pathological pregnancy. We report this rare case in a 23-year-old female, who previously had a history of recurrent miscarriages. In this case, we emphasize on clinical and histopathological features for better understanding and awareness of such rare entities.